COVID-19's Influence on China's Cross-Border Electricity Supplier and Countermeasures - Ding, Zhaijuan (International Journal of Management and Education in Human Development, 2022)
In early 2020, the spread of New Coronavirus pneumonia in China and around the world broke out rapidly, making domestic and foreign enterprises and factories shut down, and it caused a huge blow to the global economy. In order to enable China's cross-border electricity supplier enterprises and platforms to actively cope with the difficulties and challenges brought by this global major public health and safety incident, this study will explore COVID-19's influence on cross-border electricity providers and its countermeasures from various angles. Novel coronavirus pneumonia is a new technology for the development of cross-border electricity supplier. Finally, the conclusions put forward targeted suggestions for the government, platforms and enterprises.